La Resolución de Problemas en Física Clasificados por Niveles de Complejidad: Una Experiencia - Picos Rivers, Leonardo Julian; Cuador GIl, José Quintín; Martínez de Osaba Picos, Carlos Rafael (Góndola, enseñanza y aprendizaje de las ciencias, 2023)
In this paper we pretend to answer the question, how we can achieve skills in engineering students by the resolution of physics problems?. It is not possible to give an exact and definitive answer to this question, nowadays, many professors teach physics resolution problems and had presented their experiences, which has a common factor, to propose problems from the simplest to the most complex one, developing solution strategies. A classification of physical problems for complexities levels to teach physics in engineering careers is presented in this study. The solution strategies are presented using the kinematic, the dynamic and the mechanical energy conservation methods as example. The selection of problems from the texts of solution of problems used in the courses of general physics for engineering careers in Cuban´s universities was carried out, 430 problems distributed in three levels are totalized. The achievement of good results with the use of the methodology proposed is commented, from the practical experience of the authors.